Stammheim. Eine moderne Haftanstalt als Ort der Auseinandersetzung zwischen Staat und RAF - Bergstermann, Sabine (Quellen und Darstellungen zur Zeitgeschichte, 2016)
From 1974 to 1977, Stammheim was front stage in the confrontation between the state and the Red Army Faction. The terrorists effectively portrayed their conditions of imprisonment in the media as torture by isolation. Meanwhile, the state granted them privileges while tightening its legal controls. The situation came to a climax in the fall of 1977 when five prominent RAF members killed themselves while confined in Stammheim`s high-security wing